Transcriptomic analyses reveal groups of co-expressed, syntenic lncRNAs in four species of the genus Caenorhabditis - Pegueroles, Cinta (RNA Biol, 2019)
Long non-coding RNAs (lncRNAs) are a heterogeneous class of genes that do not code for proteins. Since lncRNAs (or a fraction thereof) are expected to be functional, many efforts have been dedicated to catalog lncRNAs in numerous organisms, but our knowledge of lncRNAs in non vertebrate species remains very limited. Here, we annotated lncRNAs using transcriptomic data from the same larval stage of four Caenorhabditis species. The number of annotated lncRNAs in self-fertile nematodes was lower than in out-crossing species. We used a combination of approaches to identify putatively homologous lncRNAs: synteny, sequence conservation, and structural conservation. We classified a total of 1,532 out of 7,635 genes from the four species into families of lncRNAs with conserved synteny and expression at the larval stage, suggesting that a large fraction of the predicted lncRNAs may be species specific. Despite both sequence and local secondary structure seem to be poorly conserved, sequences within families frequently shared BLASTn hits and short sequence motifs, which were more likely to be unpaired in the predicted structures. We provide the first multi-species catalog of lncRNAs in nematodes and identify groups of lncRNAs with conserved synteny and expression, that share exposed motifs.